2020
DOI: 10.1111/ina.12779
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ultrafine particles, black carbon, nitrogen dioxide, and carbon monoxide concentrations inside vehicles in the Paris area: PUF‐TAXI study

Abstract: Air pollution remains a very important risk factor for diseases and mortality worldwide. It is one of the top five leading environmental risk factors contributing to almost one death in every 10 and reducing life expectancy on average by 20 months. 1 In Europe, air pollution has been associated with about 400,000 premature deaths per year from cardiovascular and respiratory diseases. 1,2 In France, the levels of particulate matter with aerodynamic diameters ≤10 micrometers (PM 10 ) and nitrogen dioxide (NO 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…It is important to note that a number of these studies were conducted over 10 years ago, and since this time regulations for new vehicles have decreased tailpipe emissions by up to 90% particularly in European and North American locations (Anenberg et al 2017;Fiebig et al 2014). Despite more stringent emission regulations, the latest studies in 2017 and 2019 on taxi drivers in Europe found exposure to EC and BC between 3 and 9 μg/m 3 (Hachem et al 2021;Moreno et al 2019). This is a concern as a study found that a lifetime occupational exposure of 1 μg/m 3 of EC would lead to 17 excess lung cancer deaths per 10,000 individuals, above agreed occupational risk limits in the USA and Europe (Vermeulen et al 2014).…”
Section: Professional Drivers and Occupational Exposure To Diesel Exhaustmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that a number of these studies were conducted over 10 years ago, and since this time regulations for new vehicles have decreased tailpipe emissions by up to 90% particularly in European and North American locations (Anenberg et al 2017;Fiebig et al 2014). Despite more stringent emission regulations, the latest studies in 2017 and 2019 on taxi drivers in Europe found exposure to EC and BC between 3 and 9 μg/m 3 (Hachem et al 2021;Moreno et al 2019). This is a concern as a study found that a lifetime occupational exposure of 1 μg/m 3 of EC would lead to 17 excess lung cancer deaths per 10,000 individuals, above agreed occupational risk limits in the USA and Europe (Vermeulen et al 2014).…”
Section: Professional Drivers and Occupational Exposure To Diesel Exhaustmentioning
confidence: 99%
“…Only two of the studies reviewed (Baccarelli et al 2014;Davis et al 2007) sampled more than 80 shifts with the majority less than 20 and focussed on a single sector such as taxi, bus or truck drivers, making it difficult to assess whether these studies are representative of the industry as a whole. Only five out of the 16 studies employed time-resolved instrumentation (Gany et al 2017;Hachem et al 2020Hachem et al , 2021Lee et al 2015;Moreno et al 2019) using a portable aethalometer to measure BC at a 1-min time resolution. All other studies used time-integrated assessment for the duration of the drivers shift or for one study over a 24-h period.…”
Section: Professional Drivers and Occupational Exposure To Diesel Exhaustmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions from internal combustion engines account for about 70% of the most undesirable gases such as carbon oxides (CO X ), nitrogen oxides (NO X ), sulphur dioxide (SO 2 ) and hydrocarbons (Hachem et al, 2021;Hassoon, 2019;CDCP, 2013).…”
Section: Review Of the Consequences Of Chemical Constituents Impact Of Emissions From Vehicle On Human Healthmentioning
confidence: 99%
“…Since Ukraine is currently not a developed country with a stable economy, then at the current time, the population that is at the greatest risk (area of the most saturated colour, Fig. 7-9) can avoid high pollutants' concentrations in the air, mainly by closing windows and activating air conditioning in air recirculation mode (Hachem et al, 2021). If considered a category of drivers or passengers in a busy traffic flow, then in addition, smooth driving and regular maintenance of the cabin air filters should be ensured (Hachem et al, 2021).…”
Section: );mentioning
confidence: 99%